The Study Skills Handbook - Cottrell, Stella (New York Palgrave Macmillan, 2008)
If you are serious about succeeding on your course, The Study Skills Handbook is your essential companion. Based on over 20 years' experience of working with students, 1/2 million copy bestselling author Stella Cottrell helps you develop the skills you need to improve your grades, build your confidence and plan for the future you want. Her tried and trusted approach recognises that we each have a unique formula for success and that finding it is the key to reaching our potential. This book will help you to:- use your learning style and existing skills effectively - develop core study skills in time management, academic writing, critical thinking and more - discover how to make learning easier and faster - improve your grades and make study more enjoyable. Whether you are a school or college leaver, a mature student, or an international student embarking on university-level study in English for the first time, this handbook is your passport to success.